PREVALENCE OF HEPATITIS C IN DONORS FROM THE ALAGOAS BLOOD CENTER - de Santos, Fernanda Farias; de Souza, Valesca Patriota; Santos, Joelma Carvalho; de Souza, Larissa Isabella Oliveira; Bezerra, Maíza Brito Ramos; Lima, Gláucia Manoella de Souza (Saúde (Santa Maria), 2012)
http://dx.doi.org/10.5902/223658345918 In this article, we sought to assess the prevalence of hepatitis C (HCV) as well as some socio-demographic characteristics of HCV-positive blood donors of the center of Alagoas. The medical records of donors from a blood center in Alagoas were analyzed. The enzyme-linked immunosorbent assay (ELISA) was used for detection of antibodies against HCV, within the period from 2001 to 2004. Samples with positive serology by ELISA were analyzed through the confirmatory RIBA test. 45,832 donations were collected at the blood center. Out of them, 0.62% had positive serology for hepatitis C. With regard to the variables, there was a prevalence of 86.7% for males, with ages ranging from 31 to 40 years. Only 201 people returned to repeat ELISA. Out of these, 42.3% had repeated positive serology by ELISA. For confirmation by RIBA, only 97 donors returned: 55.4% were positive, 15.7% negative, and 9.1% indeterminate. The studies show the need for more specific serological screening tests.